2020
DOI: 10.1016/j.jddst.2019.101391
|View full text |Cite
|
Sign up to set email alerts
|

Matrix-based controlled release delivery of acyclovir from poly-(ethylene co-vinyl acetate) rings

Abstract: Up to 85% of the US adult population carries herpes simplex virus type-1 (HSV-1), with a smaller percentage (22%) infected with HSV-2. Herpesviruses can survive in lytic phase, when the viruses are actively replicating, or in latency, when the virus is functionally dormant in ganglia. Among drugs to treat these infections is acyclovir (ACV). ACV exhibits poor oral bioavailability and a short in vivo half-life; only about 10-15% of ingested drug enters the bloodstream and its half-life is about 3 hours. With th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…To their disadvantage, burning sensations, itchiness, and dryness were side effects noted for zinc oxide/glycerin cream and zinc sulfate gel, respectively [ 136 ]. In a recently proposed approach, Giannasca et al [ 138 ] suggested a new approach to local distribution of acyclovir via sustained drug release through the incorporation of the antiviral agent into a polymeric matrix with the shape of an antiherpetic ring. This approach showed potential improvement with respect to the efficacy of the orally administered acyclovir drug and aimed at abrogating the two main shortcomings of oral dosing, namely, poor absorption by the gut and a rapid drop in plasma concentration (cf.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To their disadvantage, burning sensations, itchiness, and dryness were side effects noted for zinc oxide/glycerin cream and zinc sulfate gel, respectively [ 136 ]. In a recently proposed approach, Giannasca et al [ 138 ] suggested a new approach to local distribution of acyclovir via sustained drug release through the incorporation of the antiviral agent into a polymeric matrix with the shape of an antiherpetic ring. This approach showed potential improvement with respect to the efficacy of the orally administered acyclovir drug and aimed at abrogating the two main shortcomings of oral dosing, namely, poor absorption by the gut and a rapid drop in plasma concentration (cf.…”
Section: Discussionmentioning
confidence: 99%
“…Applications could include the use of small fractional dispersions of Si 3 N 4 powder into indifferent creams, gels, and oral rinses (in substitution of zinc oxide and zinc sulfate) or its local exploitation via sustained hydrolytic release in polymeric matrix-based antiherpetic rings or mouthpieces. This latter approach is similar to that pursued by Giannasca et al [ 138 ], but it employs a solid-state antiviral compound rather than an absorbed drug incorporated in the polymeric matrix. Among the expected advantages, one could foresee high local effectiveness exactly at the location where herpes symptoms appear, easy maintenance, and strong prophylaxis with none of the shortcomings associated with oral uptake (e.g., poor absorption and renal metabolism of the drug before its reaching the target tissue).…”
Section: Discussionmentioning
confidence: 99%
“…For the reservoir-type rings NuvaRing ® and Ornibel ® , the exterior membranes in contact with the vaginal mucosal tissue are EVA copolymers with 9% and 28% vinyl acetate, respectively. A number of experimental drug-releasing rings fabricated from EVA are also reported [8,18,[156][157][158][159][160][161][162][163][164][165].…”
Section: Ethylene Vinyl Acetate Copolymersmentioning
confidence: 94%
“…Thermoplastic core-type VRs, such as the marketed products NuvaRing ® and Ornibel ® (Table 1), are prepared by hot melt co-extrusion. One extruder is used to compound the polymer and drug and a second extruder containing drug-free polymer is used to feed a co-extrusion die that simultaneously extrudes the active core coats in a drug-free polymer membrane [164,184,196]. With extrusion, the surface finish of the extrudate is influenced by several factors.…”
Section: Methods Of Manufacture: Injection Molding Extrusion Casting mentioning
confidence: 99%
“…Sadat concluded [22] that there are different adsorption mechanisms for acyclovir on magnetite nanoparticles with different sizes. A matrix-based antiherpetic ring composed of poly(ethylene-co-vinyl acetate) was used to release acyclovir to the vaginal epithelium [25] and New strategies based on complex nanostructures for developing advanced functional materials providing sustained release acyclovir were published recently using coreshell nano ber [26] and sericin hydrogel [27].…”
Section: Hui Et Alii Observed That the Combination Of Acyclovir And Dmentioning
confidence: 99%